Canine amniotic membrane mesenchymal stromal/stem cells: Isolation, characterization and differentiation. (June 2019) - Borghesi, Jéssica; Ferreira Lima, Mariana; Mario, Lara Carolina; de Almeida da Anunciação, Adriana Raquel; Silveira Rabelo, Ana Carolina; Giancoli Kato Cano da Silva, Marcella; Assunpção Fernandes, Fausto; Miglino, Maria Angélica; Oliveira Carreira, Ana Claudia; Oliveira Favaron, Phelipe
Graphical abstract: Through the isolation of canine amniotic membrane cells it was possible to verify that these cells do not present tumorigenic potential and present a positive immunophenotype fro CD105, PCNA and MHCI and negative for CD34 and MHC II. In addition, they are able to differentiate into adipogenic, osteogenic and chondrigenic lines. Highlights: Canine amniotic membrane cells have characteristics of mesenchymal stem cells. Differentiation in the three embryonic lineages. Biosafety verified for in vivo application. Abstract: The amniotic membrane can be considered as one of the sources of isolation of these cells, since it is found in the fetal maternal interface and has low immunogenicity. Mesenchymal stromal/stem cells (MSCs) have not been identified in canine amniotic membrane (AMC). Therefore, our objective was to isolate, culture, characterize and differentiate cells derived from canine amniotic membrane (AMC) and to verify its immunological and tumorigenic potential. For this, 12 dogs fetuses of each gestational age 32, 43 and 55 days were used, and the isolation and culture of the AMC were performed. We observed that the cells presented fibroblastoid morphology and high confluence even after freezing. We also observed that, when induced, they were able to differentiate into osteogenic, adipogenic, and chondrogenic cells, as well as being CD34- and CD105+. Regarding the immunological markers, we found that IL-1, IL-2, IL-6, IL-10 and MHC II were not expressed, whereas MHC I was expressed. After application of AMC cells in nude mice we can verify that there was no tumor formation. Based on this, we conclude that canine amniotic membrane is a good and accessible source for obtaining MSCs of low immunogenic and tumorigenic potential for veterinary therapeutic applications.